Analysis Implementation of the Standard Model Higher Education Financing - Kwartawaty, Nana Noviada; Widyaatmadja, Swanny Trikajanti; Jona, Resa Nirmala (Asian Journal of Management Analytics, 2025)
Finance and financing own very important role in support effectiveness and efficiency management education. Due its benefits are widespread and impactful various sector, funding education should become focus main for government and society. Refers to principles that, problem financing becomes very important For investigated. Therefore that's the goal from study This is For evaluate application of the standard model financing education tall. Writing method article scientific This use approach qualitative and literature reviews. In qualitative research, literature reviews must be used consistently with methodological assumptions. Data sources include documents and literature studies. The research results show that, in general, there are three basic models of higher education financing, meaning the bureaucratic, collegial and market models. A comparative analysis of the advantages and disadvantages of these models shows that the most efficient and flexible model is the market model because it allows higher education institutions to diversify their funding sources, attract additional resources using financial markets and invite donors by guaranteeing continuous control over their donations.